1991
DOI: 10.1136/thx.46.2.91
|View full text |Cite
|
Sign up to set email alerts
|

Plasma tumour necrosis factor alpha in cystic fibrosis.

Abstract: Plasma tumour necrosis factor alpha (a) concentration is increased in acute Gram negative sepsis, but the effect of chronic infection on plasma concentrations is unknown. A study was carried out in patients with cystic fibrosis to determine the effect of chronic lung infection with Pseudomonas aeruginosa on the plasma concentration of tumour necrosis factor and two other indicators of the inflammatory response, circulating C reactive protein and neutrophil elastase-a, antiproteinase complex (elastase complex).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
1
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 21 publications
3
51
1
1
Order By: Relevance
“…Pulmonary inflammation and consequent injury is linked to systemic inflammation in patients with COPD, 29 and increased circulating inflammatory markers have been detected in CF subjects. 30,31 Infection induces respiratory muscle weakness in animal models, 32 and respiratory muscle weakness is associated with upper-respiratory-tract infections in humans. 33 Induced chronic bronchopulmonary infection by P. aeruginosa significantly decreased diaphragm and limb strength in infected mice, 28 and tumor necrosis factor alpha depressed the diaphragmatic tetanic force in murine diaphragm and limb muscle preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary inflammation and consequent injury is linked to systemic inflammation in patients with COPD, 29 and increased circulating inflammatory markers have been detected in CF subjects. 30,31 Infection induces respiratory muscle weakness in animal models, 32 and respiratory muscle weakness is associated with upper-respiratory-tract infections in humans. 33 Induced chronic bronchopulmonary infection by P. aeruginosa significantly decreased diaphragm and limb strength in infected mice, 28 and tumor necrosis factor alpha depressed the diaphragmatic tetanic force in murine diaphragm and limb muscle preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have observed that pHLE complexes are increased in the blood of patients with CF [19,[29][30][31]. Increases in pHLE complexes have been reported in various studies of oxidant stress, antioxidant supplementation and other aspects of CF lung disease [31][32][33][34]; however, other investigators have found that HLE complexes in the blood of CF patients do not re ect respiratory exacerbations and do not correlate with lung function [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, a systemic marker may not be sensitive enough to detect a meaningful change in lung disease, given that the inflammatory response to infection in the CF lung is largely confined to the lung. Assessments in blood have included antibodies to Pseudomonas aeruginosa (81)(82)(83) or products of inflammation (84), neutrophil elastase ␣ 1 -antiprotease complexes (63,85), C-reactive protein (CRP) (85,86), and various cytokines from serum or plasma (27,(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97), and blood cells themselves (32,33,(98)(99)(100)(101)(102)(103). C-reactive protein is gaining increased recognition as a marker of inflammation for other diseases, but in CF, it is widely variable due to transient increases during pulmonary exacerbations (104,105).…”
Section: Assessing Inflammation In the Cf Lungmentioning
confidence: 99%